Investigating the Use of Lime Kiln Dust as a Filler in Asphalt Concrete for Durable Flexible Pavements - Mohammed Mbarak (Uganda Christian University, 2024)
Flexible pavements, primarily used in Uganda, are roadways composed of a blend of bitumen, mineral filler, and aggregates. The main aim of this study was to investigate the use of lime kiln dust as a mineral filler in asphalt concrete for durable flexible pavements, in proportions by mass of the active filler. The main methods used were the Marshall test, determination of engineering properties of the mineral filler, bitumen, and aggregates, as well as Indirect Tensile Strength (ITS) testing on the asphalt mixtures. During the study, various factors were evaluated, encompassing Marshall stability, flow characteristics, unit weight, air voids (VA), voids filled with asphalt (VFA), and voids in the mineral aggregate (VMA). The results showed that the use of lime kiln dust led to a reduction in air voids from 5.7% to 4.9%, an increase in Marshall stability from 14.8 to 17.1, increased Indirect Tensile Strength Wet Strength from 81% to 90%. This implied that the incorporation of 4% lime kiln dust filler improved the rutting resistance of asphalt mixtures by enhancing the stability and stiffness of the mix. However, further studies should consider a batch total mass of the mix of 18,000g, with proportions of 882g of bitumen, 856g of 14/20, 1198g of 10/14, 2568g of 6/10, 11,811g of 0/6 aggregates, and 685g of LKD filler in the mix design. Additionally, the effect of temperature on the storage of filler material should be investigated to assess fatigue response, as it affects the filler composition and, in turn, the strength performance properties of asphalt.